Enhanced Thermoelectric Power Factor of NaxCoO2 Thin Films by Structural Engineering. Issue 8 (12th February 2014) - Brinks, Peter; Kuiper, Bouwe; Breckenfeld, Eric; Koster, Gertjan; Martin, Lane W.; Rijnders, Guus; Huijben, Mark
<x xml:space="preserve">Abstract</x> By controlling the crystallinity and average grain size of thermoelectric NaxCoO2 thin films, a doubling of the thermoelectric power factor is achieved in combination with a strong suppression of the thermal conductivity. These structurally engineered NaxCoO2 thin films outperform single crystalline and polycrystalline samples at room temperature and demonstrate the potential of thermoelectric oxide thin films. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>